1999
DOI: 10.1021/jo981972g
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Stereoselection in Tethered Biginelli Condensations. Synthesis of cis- or trans-1-Oxo- and 1-Iminohexahydropyrrolo[1,2-c]pyrimidines

Abstract: Stereoselection in tethered Biginelli condensations can be tuned to give either the cis or trans stereoisomer of 1-oxohexahydropyrrolo[1,2-c]pyrimidine and 1-iminohexahydropyrrolo[1,2-c]pyrimidine products (see eq 1). With substrates having urea and N-sulfonylguanidine functionality (Schemes 2 and 4), cis stereoselection (4-7:1) is observed when the condensation is accomplished under Knoevenagel conditions, while trans stereoselection (4-20:1) is observed when the condensation is carried out in the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 26 publications
3
48
1
Order By: Relevance
“…These workers showed that higher yields, and in some cases higher stereoselectivities, were realized in polar, protic solvents such as methanol or trifluoroethanol. 24 Renhowe also found that the reaction gave higher yields and improved stereoselectivity in the presence of morpholinium acetate (pK a = 8.3) than with piperidinium acetate (pK a = 11.1). 25 Intermediates such as 14 are complex mixtures that contain traces of the acyclic ureido aldehyde, the depicted 2-hydroxypyrrolidine isomer, as well as higher molecular weight oligomers.…”
Section: Tethered Biginelli Condensationsmentioning
confidence: 95%
“…These workers showed that higher yields, and in some cases higher stereoselectivities, were realized in polar, protic solvents such as methanol or trifluoroethanol. 24 Renhowe also found that the reaction gave higher yields and improved stereoselectivity in the presence of morpholinium acetate (pK a = 8.3) than with piperidinium acetate (pK a = 11.1). 25 Intermediates such as 14 are complex mixtures that contain traces of the acyclic ureido aldehyde, the depicted 2-hydroxypyrrolidine isomer, as well as higher molecular weight oligomers.…”
Section: Tethered Biginelli Condensationsmentioning
confidence: 95%
“…[14,48] The reaction has also been realized in an asymmetric manner. [49][50][51][52] Total synthesis of natural polycyclic guanidine alkaloids has been accessed by the Biginelli reaction by simply replacing urea with a suitable guanidinium component. [53][54][55] The Biginelli reaction was ultimately exploited in material chemistry as direct, convergent and easy reaction for the development of functional materials such as polymers, dyes or adhesives.…”
Section: The Biginelli Reactionmentioning
confidence: 99%
“…5 Modified ap-proaches to DHPM synthesis, for example those proposed by Atwald and Shutalev, 6 have also been reported. The condensed DHPM nucleus of the alkaloids batzelladines B and D was constructed using the condensation between acetoacetic ester and a complex derivative of N-a-hydroxyalkyl urea; 7 in a more recent example, vinyl carbodiimides were cycloadded to chiral cyclic imines. 8 To obtain partially hydrogenated derivatives of pyrrolo [1,2c]pyrimidine, constituting the heterocyclic system of saxitoxin, Kishi suggested the condensation of 2-carbethoxymethylidenepyrrolidine with isocyanic acid and acetaldehyde.…”
Section: Figurementioning
confidence: 99%